Experimental design and analysis and their reporting II: updated and simplified guidance for authors and peer reviewers. (9th March 2018) - Curtis, Michael J; Alexander, Steve; Cirino, Giuseppe; Docherty, James R; George, Christopher H; Giembycz, Mark A; Hoyer, Daniel; Insel, Paul A; Izzo, Angelo A; Ji, Yong; MacEwan, David J; Sobey, Christopher G; et al.
Abstract: This article updates the guidance published in 2015 for authors submitting papers to British Journal of Pharmacology (Curtis et al., 2015) and is intended to provide the rubric for peer review. Thus, it is directed towards authors, reviewers and editors. Explanations for many of the requirements were outlined previously and are not restated here. The new guidelines are intended to replace those published previously. The guidelines have been simplified for ease of understanding by authors, to make it more straightforward for peer reviewers to check compliance and to facilitate the curation of the journal's efforts to improve standards.